2019
DOI: 10.2147/bctt.s181730
|View full text |Cite
|
Sign up to set email alerts
|

<p>The antiestrogenic effects of black cohosh on BRCA1 and steroid receptors in breast cancer cells</p>

Abstract: Background Black cohosh (BC) is an herbal remedy often used by women to treat symptoms associated with menopause. Research has shown that the molecular activity of BC is associated with estrogen receptor alpha (ER-α) regulation. Progesterone receptor (PR) expression is found to be consistent with ER expression and mutations in the BRCA1 gene, a tumor-suppressor gene, are known to be responsible for about 40%–45% of hereditary breast cancers. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Western blotting was performed using the Bio-Rad general protocol ( 38 ). Cell lysates were prepared from lung cancer cells (H292, CL1-5, PC-9 and H460) and NHBE cells and total protein were subsequently extracted using (1X) radioimmunoprecipitation assay (RIPA) buffer (cat.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed using the Bio-Rad general protocol ( 38 ). Cell lysates were prepared from lung cancer cells (H292, CL1-5, PC-9 and H460) and NHBE cells and total protein were subsequently extracted using (1X) radioimmunoprecipitation assay (RIPA) buffer (cat.…”
Section: Methodsmentioning
confidence: 99%
“…The membranes were treated for 2 h at room temperature with each secondary antibody from the mouse and rabbit. Following ECL color development, data for photography were collected using Bio–Rad imaging equipment [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…USP recommends CR products must be labelled with a cautionary statement such as: "Discontinue use and consult a healthcare practitioner if you have a liver disorder or develop symptoms of liver trouble, such as abdominal pain, dark urine, or jaundice". Nevertheless, the U.S. FDA does not need such caution on labels of CR products [125] The American Herbal Products Association, 2013…”
Section: Health Risksmentioning
confidence: 99%
“…One of the latest studies claimed that CR revealed significant anti-cancer properties on the expression of PR, ER-α, and BRCA1 in MCF-7 and T-47D mammary cancer cell lines. Furthermore, they revealed that in presence of CR, the proliferative action of estrogen was decreased, hence altering the growth of hormone-dependent mammary cancer cells [ 125 ]. Another study investigating the effects of standardized CR extract and its key triterpene actein on growth rates and the metabolism of the steroid hormone in human breast cancer cell lines concluded that it did not promote cell growth in breast cancer cell lines, or have any impact on estrogen concentration.…”
Section: Pharmacology and Biochemistry Of Cr Extract/biological Chara...mentioning
confidence: 99%